WILLINGNESS TO PAY FOR HYDROPONIC VEGETABLES IN SAMBAS DISTRICT - Uray Dian Novita; Wilis Widi Wilujeng; Khaironisa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Hydroponics is one of the vegetable cultivation techniques that is beginning to develop in Sambas. In addition to its stable price range of IDR 5,000 - IDR 6,000 per 200 gram package, consumers prefer it because the vegetables tend to be healthier and cleaner than similar vegetables grown in soil. This study aims to analyze consumer willingness to pay (WTP) for hydroponic vegetables in Sambas District. The research method used is the Contingent Valuation Method (CVM) with data collection through surveys of consumers who have purchased or are interested in hydroponic vegetable products. Data collection was carried out in several locations that are centers for hydroponic vegetable cultivation. The results of the study show that the average WTP that consumers are willing to pay for hydroponic vegetables in Sambas is IDR 6,980 per 200 gram package. Household income and expenditure have very little influence on the purchase of hydroponic vegetables. These findings indicate the market potential for hydroponic vegetable products in Sambas, even though the WTP value of consumers in this region is relatively lower than the results of studies in other regions, which are generally influenced by factors such as health awareness, product quality, and environmental concerns. The results of this study are expected to serve as a reference for business actors and policy makers in the development of the hydroponic vegetable agribusiness in Sambas, particularly in determining pricing and promotion strategies that are in line with the purchasing power and preferences of local consumers.